Additive equations for estimating aboveground biomass of Pinus cembroides Zucc. - Cuevas Cruz, Juan Carlos; Aquino Ramírez, Martín (Instituto de Ecología, A.C., 2020)
Allometric equations are an important tool for accurate estimation of aboveground biomass of trees and their components. This document presents additive equations for estimating aboveground biomass in Pinus cembroides Zucc trees. In October 2017, a total of 21 trees of different diameter classes (5 cm to 40 cm) were felled and sectioned into three structural components: stem, branches and twigs with leaves to obtain their biomass. Two systems of non-linear equations were developed, in which the additivity was guaranteed by establishing the total aboveground biomass (Bt) as the sum of the biomass estimates of each component of the tree. The system that integrated the diameter at breast height and the total height of the tree as predictor variables explained more than 92% of the variation observed in the biomass data of the components and 98% of variability of the Bt. The average proportion of biomass in the stem, branches and twigs with leaves comprised 43.2%, 41.2% and 15.5% of the tree Bt, respectively. The equations generated in this study will contribute to improve the precision in biomass estimation and carbon inventories in P. cembroides forests.